2012
DOI: 10.1002/cyto.a.22111
|View full text |Cite
|
Sign up to set email alerts
|

Bleaching response of Symbiodinium (zooxanthellae): Determination by flow cytometry

Abstract: Coral bleaching is of increasing concern to reef management and stakeholders. Thus far, quantification of coral bleaching tends to be heavily reliant on the enumeration of zooxanthellae, with less emphasis on assessment of photosynthetic or physiological condition, these being often assessed separately by techniques such as liquid chromatography. Traditional methods of enumeration using microscopy are time consuming, subjected to low precision and great observer error. In this study, we presented a method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Kleinegris et al reported that the 560 nm fluorescence of the green microalga Dunaliella salina was emitted by β-carotene (excitation at 488 nm). In Symbiodinium , the green fluorescence signal in FL1 (529 ± 28 nm band-pass filter) was generally used for β-carotene analysis [ 43 ]. These results demonstrated that the fluorescence intensities at the range of 530–580 nm had a close relationship with carotenoids, which was the foundation of the FCM method for astaxanthin analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Kleinegris et al reported that the 560 nm fluorescence of the green microalga Dunaliella salina was emitted by β-carotene (excitation at 488 nm). In Symbiodinium , the green fluorescence signal in FL1 (529 ± 28 nm band-pass filter) was generally used for β-carotene analysis [ 43 ]. These results demonstrated that the fluorescence intensities at the range of 530–580 nm had a close relationship with carotenoids, which was the foundation of the FCM method for astaxanthin analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Standardization to protein content did not alter the interpretation of treatment effects (Figure S7, Table S3), so we focus on surface area standardized responses (Figure 2). Symbiodiniaceae densities were quantified using flow cytometry ((Lee et al., 2012); Figure S5). Chlorophyll a (chl‐a) and chl‐c were extracted in 100% acetone at −20°C for 36 hr and quantified following Jeffrey and Humphrey (1975).…”
Section: Methodsmentioning
confidence: 99%
“…Other processes affected by inhibition of DNA methylation included the changes in cellular size and the pigment chl c2 level, as well as autofluorescence. The autofluorescence profiles of algal cells cultures undergoing thermal stress provide information on the dynamics of photosynthetic pigments such as chlorophyll a and chlorophyllc2 , both specialised in harvesting light, and accessory pigments such as carotenoids that serve photo-protective functions (Olson et al 1989, Lee et al 2012.…”
Section: Discussionmentioning
confidence: 99%